Germinal Center B cells provide essential IL-1β signals to TFH cells via canonical NLRP3 inflammasome activity post influenza infection - Restrepo Munera, Juliana; Riccio-Baum, Cainan; Kaddis Maldonado, Rebecca; Allie, S. Rameeza (PLOS Pathogens, 2025)
Persistent germinal center (GC) responses show increased benefit in optimal responses to influenza infection. Follicular helper T (TFH) cells provide the essential signals and help for maintenance of GCs and require IL-1β signaling for establishment and maintenance. We observe a preferential upregulation of IL-1β within GC B cells and coexpression of NLRP3 and caspase-1 with IL-1β confirms that GC B cells process IL-1β using a canonical NLRP3/caspase-1 mechanism. Using B cell specific ablation of IL-1β production and IL-1β signaling we further confirm that, GC B cells are the primary source of vital IL-1β within the GC and that IL-1β processing by GC B cells post influenza infection is driven by NLRP3 inflammasomes. We observe significant reduction of GC B cells and TFH cells in the absence of B cell derived IL-1β and our analysis of human B cells suggests similar mechanisms in human GC B cells. Our data present GC B cells in two novel roles, the first in producing IL-1β, which is associated with innate functions, within the GC and the second is providing helper cytokine to the TFH cell. Our findings add to the known complexity of the GC providing a target to enhance GC function and persistence.